Evaluasi Teknis Geometrik Jalan pada Ruas Jalan Menuju Bandara Syamsudin Noor: Geometric Road Evaluation on Syamsudin Noor Airport Road - Emma Ruhaidani; Amelia Faradila; Dyah Pradhitya Hardiani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Syamsudin Noor Airport is located in Landasan Ulin District, Banjarbaru City, South Kalimantan Province. The geometric condition of the road on the new road to Syamsudin Noor Airport has a horizontal arrangement of several bends that are not comfortable for road users. The corners reviewed there are 2 corners at STA 3+140 and STA 3+580. The purpose of this study is to evaluate the existing conditions using the 1997 Bina Marga standard and Re-design using the 2021 Bina Marga standard. The research method used in this study is an analysis method of existing conditions using the 1997 Bina Marga standard and Re-design using the 2021 Bina Marga standard. As for the data on field speed, road width, shoulder width, road traffic and visibility are obtained through direct measurements and observations. Based on the results of research conducted in the field, the existing geometric conditions of the road were obtained, in the existing conditions the speed from the observation results was used 64 Km / Hour. The condition at turn 1 has a value of Rc > Rmin so that it meets the requirements of the 1997 Bina Marga standard, while at turn 2 it does not meet because Rc < Rmin. The superelevation at turns 1 and 2 did not meet the 1997 Bina Marga standard of en = 2%.